Being Prepared: Prospective Teachers' Expectations of Addressing Indigenous Students' Needs in a Critical Literacy Framework - Cherubini, Lorenzo (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
The education of Indigenous students in Ontario’s publicly-funded schools remains concerning. Given the socio-historical marginalization of Indigenous student epistemologies in public education it is necessary for teachers to account for Indigenous students’ learning needs, and to examine their own assumptions as teachers. Among those positioned to speak of Indigenous students’ experiences in public schools are prospective teachers who complete teaching-practicums in different of schools. This mixed-methods study focuses on the expectations of over 200 prospective teachers prior to any practicum-related experiences in the classroom. It investigates prospective teachers’ perceptions of the extent to which their professional teacher education program will prepare them to address competently Indigenous students’ learning needs and to examine their assumptions as teachers of bicultural students.